Christian Oxyrhynchus : texts, documents, and sources - Blumell, Lincoln H., 1975-; Wayment, Thomas A. (Baylor University Press, 2015)
"Authoritative, comprehensive presentation of Christian texts and texts about Christians in the Oxyrhynchus papyri"--